Evaluative Studies of Project-Based Mathematical Learning: Reviewed from National Standard for Education Process in Indonesia - Pujawa, I Gusti Ngurah; Suryawan, I Putu Pasek; Ariawan, I Putu Wisna (FKIP Universitas Lampung, 2022)
Evaluative Studies of Project-Based Mathematical Learning: Reviewed from National Standard for Education Process in Indonesia. Objectives: To describe the effectiveness of the implementation of project-based learning in junior high school mathematics learning in terms of process standards. Methods: This study adopted the CIPP evaluation model with state junior high school mathematics teachers as respondents.The analysis technique refers to the calculation of the T score in consultation with the Glickman quadrant prototype. Findings: T score for each variable, namely CIPP (+ - + +) with a comparison for the Context variable: F+ (71.43%) and F- (28.57); Inputs: F+ (28.57%) and F- (71.43%); Process: F+ (71.43%) and F- (28.57%), Product: F+ (71.43%) and F- (28.57%) with quite effective category. Conclusion: Project-based mathematics learning in terms of process standards is quite effective, and can be recommended to improve the quality of mathematics learning. Keywords: evaluation of mathematical learning, project-based learning, process standards.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202218